2021
DOI: 10.5334/aogh.3142
|View full text |Cite
|
Sign up to set email alerts
|

Association of Life-Course Educational Attainment and Breast Cancer Grade in the MEND Study

Abstract: Background: Nigeria reports the highest age-standardized mortality rate for breast cancer (BC) among African countries and disproportionately high rates of high-grade cancer. Histological grade is a strong predictor of mortality, and evidence suggests that educational attainment influences cancer outcomes.Objective: We characterize the association between educational trends across the lifecourse and BC grade at diagnosis. Methods: Data on 224 BC patients enrolled in the Mechanisms for Established and NovelRisk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The prevalence of obesity is growing worldwide and more than 15% of adults in most countries are classified as obese [26], then, it is likely that the trends in increasing incidence in postmenopausal age are the result of the growing importance of obesity as a risk factor for cancer worldwide [27]. In addition, there are studies where it was found that people with a stable high level of education in relation to the father were more prone to low-grade cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity is growing worldwide and more than 15% of adults in most countries are classified as obese [26], then, it is likely that the trends in increasing incidence in postmenopausal age are the result of the growing importance of obesity as a risk factor for cancer worldwide [27]. In addition, there are studies where it was found that people with a stable high level of education in relation to the father were more prone to low-grade cancer [28].…”
Section: Discussionmentioning
confidence: 99%